Decolonization in “Wild Schools”: Local Music Pedagogies in Indonesia’s Taman Siswa School System - Irwin, Gillian (Intersections, 2019)
Ten years after the Taman Siswa (Garden of Students) schools were founded in 1922, the Dutch colonial government declared them Wilde Scholen (Wild Schools) for operating without government certification. Taman Siswa educators resisted the designation, eventually repealing the ordinance, as an act of rebellion against colonization. Decades after Indonesia achieved independence, Taman Siswa continues to work towards decolonization by focusing on student self-governance and local wisdom, two core pedagogies of Taman Siswa founder Ki Hadjar Dewantara that are practised daily in music classrooms. Ultimately, I argue for a closer examination of Taman Siswa as an educational institution striving for decolonization in complex regional, national, and global systems.